Translation Techniques Used in the English Version of Andmesh Kamaleng Song’s Hanya Rindu Translated by Emma Heesters - Pramudita Maharani Ayuningtyas Atmojo; Raden Arief Nugroho (Yayasan Visi Intan Permata, 2025)
This research aims to explore the translation techniques that implemented at English version from Andmesh Kamaleng’s song titled Hanya Rindu which Emma Heesters translated it using the group of 18 techniques of translation from Albir & Molina (2002). This study implements a descriptive qualitative approach to examine the techniques which applicated on translating Indonesian song lyrics into English. Data were collected from the English version of the song lyrics and the original Indonesian version. This study utilized content analysis and note-taking, the steps are as follows: 1) listen to and observe the lyrics of both versions of the song; 2) identify the categories from the usage techniques of translation; 3) make a conclusion. The study identified 9 out of 18 possible translation techniques used in 48 sample lyrics. The findings show that amplification is the most frequently used technique which is 12 times (25%), followed by literal translation 9 times (19%) and modulation 9 times (19%), linguistic amplification 7 times (15%), transposition 4 times (8%), reduction 3 times (6%), linguistic compression 2 times (4%), generalization 1 time (2%) and 1 time discursive creation (2%). The prevalent use of amplification indicates the translators' tendency to add contextual elements to enhance clarity and maintain the emotional context of the song, as well as to make the translated lyrics match the melody so that it is singable. The findings of this study contribute to a deeper understanding of song translation and expose the challenges faced by translators in preserving song messages across languages.